The epistemic power of the police - Boutros, Magda (Theoretical criminology, 2024)
This article uses movements against police brutality as a starting point to rethink our theorizations of police power, asking how the police maintain their dominance over oppressed groups, and what it takes to challenge it. I argue that an important, but undertheorized dimension of police power is epistemic power, the ability to control what is known and what remains unknown about policing practices. Epistemic power derives from (1) the police's control over the production and non-production of data about crime and policing; (2) the assumption that police officers are more credible than their targets; and (3) their privileged access to the media. Using France as a case study, I show how the police draw on epistemic power to produce ‘truth’ and manufacture ignorance about their practices, and I examine activist strategies to challenge and disrupt this power.